A study of Sarawak ethnic food "Tuak" as means of communication in understanding culture / Nik Mohd Shahril Nik Mohd Nor ... [et al.] - Nik Mohd Nor, Nik Mohd Shahril; Mohamed Idris, Aida Khalida; Hashim, Norliana; Tarmazi, Siti Anis Adilah; Dawi, Siti Dorsiela (Universiti Teknologi MARA Cawangan Pahang, 2020)
At present, food is more than just a means or an imperative element of survival. Some food is related to society, religions, continuity, culture and identity. Iban, Bidayuh, Malay, Melanau, Chinese, Sebob and Orang Ulu are among the natives' groups of who populates the largest state of Malaysia and each group owned their uniqueness of ethnic natives' food identity and cultures. Sarawak is culturally rich in terms of its various races, religions, languages, and celebrations. Therefore, present study aims to study on the Sarawak ethnic natives' traditional food "Tuak" as means to communicate in the Iban culture. Other researches study has been reviewed in filling the gap of understanding Sarawak culture through food communication. "Tuak" (alcoholic beverage made from rice wine) is one of the most cultural identities associated with the Iban ethnic and is very popular during the Gawai Dayak festive. Gawai relies on Tuak as an offer of thanksgiving to rice spirit for a bountiful harvest and also as a sign of gratitude and in requesting Petara for more blessings, long life and prosperity. In conclusion, this study highlighted the importance of the Sarawak ethnic food Tuak towards food symbolism as it represents an image of Iban culture, religions and festival which needed to be well protected and maintained and if it is not done so, it will not make a distinction or faded among the society.